Patient-Identified Quality Indicators for Colonoscopy Services - Maida J Sewitch; Catherine Dubé; Stephanie Brien; Mengzhu Jiang; Robert J Hilsden; Alan N Barkun; David Armstrong (Canadian Journal of Gastroenterology)
BACKGROUND: Current quality improvement tools for endoscopy services, such as the Global Rating Scale (GRS), emphasize the need for patient-centred care. However, there are no studies that have investigated patient expectations and/or perceptions of quality indicators in endoscopy services.